The Mutual Growth of International and National Emergency Medical Teams (EMT): Synergetic Growth and Reinforcement Between Japan’s Disaster Relief Team and Disaster Medical Assistance Team - Koido, Yuichi; Toyokuni, Yoshiki; Ariani, Madelina; Kubo, Tatsuhiko; Iimura, Tsutomu; Oba, Jiro (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: Japan, situated on the seismically active Pacific Ring of Fire, frequently experiences natural disasters. Consequently, Japan’s disaster medical response system has evolved significantly, leveraging both international and domestic experiences. This study reports the development of Japan’s disaster medical teams, emphasizing the synergistic relationship between international and domestic response efforts while highlighting key milestones in the system’s evolution. Methods: This study utilizes a case study approach to report the historical evolution of Japan’s disaster medical response system. Data were gathered through document reviews and a rapid review approach, which assessed major events and structural developments. Results: Japan’s early international disaster medical efforts began with its response to the Cambodian refugee crisis in the 1970s, leading to the establishment of JMTDR and later JDRT. Domestically, the Great Hanshin-Awaji Earthquake in 1995 catalysed the establishment of DMAT and Japan NDMS. The J-SPEED system, inspired by international deployments, further standardized WHO EMT for rapid and informative medical data collection. Conclusion: The evolution of Japan’s disaster medical teams highlights key milestones and the synergetic collaboration between JDRT and DMAT. Japan’s international and domestic disaster response systems have facilitated the advancement of disaster response capabilities, leading to more sophisticated response abilities.